Ambivalent Encounters - Huberman, Jenny (Rutgers University Press, 2021)
Jenny Huberman provides an ethnographic study of encounters between western tourists and the children who work as unlicensed peddlers and guides along the riverfront city of Banaras, India. She examines how and why these children elicit such powerful reactions from western tourists and locals in their community as well as how the children themselves experience their work and render it meaningful.